Symmetric Dimethylarginine as a Biomarker for Chronic Kidney Disease - Khairat AS; Harnavi Harun; Deka Viotra (HM Publisher, 2023)
Symmetric dimethylarginine (SDMA), is a post-translationally stable catabolic product of arginine-methylated proteins that plays an important role in basic cellular metabolism. SDMA is an endogenous biomarker of kidney function that has been widely used in veterinary medicine. Symmetric dimethylarginine (SDMA) and asymmetric dimethylarginine (ADMA) are 2 constant products of L-arginine proteolysis that undergo methylation. SDMA is almost completely excreted by the kidneys after filtration making SDMA an ideal GFR biomarker candidate. Apart from that, SDMA has several advantages as a biomarker of kidney function, namely that it is not affected by non-renal factors that influence creatinine and cystatin C. Apart from that, SDMA also increases earlier than other biomarkers.